Analisis Fitur Aplikasi Japanese Kanji Study sebagai Media Pendukung Pembelajaran Bahasa Jepang (Jurnal Sistem Informasi dan Ilmu Komputer, 2025)
Mastering kanji characters is a crucial aspect of learning the Japanese language, yet many beginner learners face challenges in memorizing their forms, meanings, and readings. To support independent learning, digital applications such as Japanese Kanji Study offer practical and flexible alternatives. This study aims to analyze the features of the Japanese Kanji Study application and evaluate its effectiveness as a learning medium. The research adopts an exploratory qualitative approach, involving a seven-day direct investigation of the application’s core features, along with user reflection and comparison with two similar applications. The results indicate that Japanese Kanji Study provides a user-friendly interface, content organized by JLPT levels, and features that facilitate understanding of meanings, readings, and stroke order of kanji. Over the exploration period, the author successfully learned 35 N5-level kanji characters. User reflections show that the application is effective in improving kanji comprehension, although further development is needed in terms of interactivity and learning motivation. In conclusion, Japanese Kanji Study serves as a valuable self-learning tool for kanji, particularly for beginner learners.